(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
Global suicide rates have increased 60% in the past 45 years. Its incidence is also high in India and the mode of suicide is hanging in majority of cases. This retrospective study was conducted on 92 postmortem cases of hanging victims at government medical college Bhavnagar, Gujarat (A tertiary care centre) morgue over a period of one year (1st January 2017 to 31st December 2017). The Objectives of this study is to find out profile of hanging, its distribution according to age group, sex, most common ligature material used by victim and place of hanging. Total of 1057 medico legal autopsies were conducted during this study period.Out of 92 cases, 66 (71.7%) were male and 26 (28.3%) were female.43(46.7%) victims were from the age group 21-30 years. Dopatta (odhna) was the commonest (38 cases, 41.3%) ligature material followed by rope (30 cases, 32.6%).